Analysis of Digital Competency Management in Enhancing the Soft Skills of Vocational High School Students - Desi Sri Sulistia (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
The advancement of digital technology requires vocational education institutions to equip students not only with technical skills but also with relevant soft skills to face the dynamics of the creative industry. This study aims to analyze the management of digital competence in enhancing the soft skills of students at SMK Nurul Huda Al-Ghina Cimerak. The research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings indicate that the management of digital competence at the school is not yet fully integrated into the curriculum but has been initiated through multimedia projects based on practical assignments. Students’ soft skills, such as communication, collaboration, and initiative, have begun to develop, although aspects such as self-regulation and discipline still require further attention. The correlation between digital technology proficiency and soft skill enhancement is evident through the implementation of project-based learning models. Supporting factors include the active role of teachers and the disciplined pesantren (Islamic boarding school) culture, while the inhibiting factors involve limited infrastructure, insufficient teacher training, and a lack of collaboration with industry. Therefore, an integrative managerial strategy is needed to simultaneously strengthen digital competence and soft skills within the vocational education ecosystem.